Utilization of Canva for education to improve learning effectiveness of vocational students - M. Muhajir; Ayu Sarwendah; Abdullah bin Ibrahim (Universitas Muhammadiyah Malang, 2024)
Canva for education is a version of Canva designed specifically for education. The results of the literature review show that the learning effectiveness of SMK students is not optimal. This is because teachers only use passive and non-interactive learning media, such as showing pictures or videos without providing opportunities for students to actively participate in learning. This study aims to determine the use of canva for education to improve the learning effectiveness of vocational students. The method used in this study is SLR (Systematic Literature Review) which consists of 15 published journal samples. Data collection techniques are carried out by collecting some relevant previous research, then compiled, analyzed, and concluded. Based on the results of research that has been carried out, canva for education can increase the learning effectiveness of vocational students The use of canva for education can increase the learning effectiveness of vocational students because it attracts students' interest, makes learning materials easier to understand, develops graphic design skills and strengthens collaboration, thereby increasing student motivation and learning outcomes. The use of Canva for education should be balanced with effective learning strategies.